Interface Symbiotic Membrane Formation in Root Nodules of Medicago truncatula: the Role of Synaptotagmins MtSyt1, MtSyt2 and MtSyt3 - Gavrin, Aleksandr; Kulikova, Olga; Bisseling, Ton; Fedorova, Elena E. (Frontiers in Plant Science, 2017)
Abstract Symbiotic bacteria (rhizobia) are maintained and conditioned to fix atmospheric nitrogen in infected cells of legume root nodules. Rhizobia are confined to the asymmetrical protrusions of plasma membrane (PM): infection threads, cell wall-free unwalled droplets and symbiosomes. These compartments rapidly increase in surface and volume due to the microsymbiont expansion, and, remarkably, the membrane resources of the host cells are targeted to interface membrane quite precisely. We hypothesized that the change in the membrane tension around the expanding microsymbionts creates a vector for membrane traffic toward the symbiotic interface. To test this hypothesis, we selected calcium sensors from the group of synaptotagmins: MtSyt1, Medicago truncatula homolog of AtSYT1 from Arabidopsis thaliana known to be involved in membrane repair, and two other homologs expressed in root nodules: MtSyt2 and MtSyt3. Here we show that MtSyt1, MtSyt2 and MtSyt3 are expressed in the expanding cells of the meristem, zone of infection and proximal cell layers of zone of nitrogen fixation (MtSyt1, MtSyt3). All three GFP-tagged proteins delineate the interface membrane of infection threads and unwalled droplets and create a subcompartments of PM surrounding these structures. The localization of MtSyt1 by EM immunogold labelling has shown the signal on symbiosome membrane and endoplasmic reticulum (ER). To specify the role of synaptotagmins in interface membrane formation, we compared the localization of MtSyt1, MtSyt3 and exocyst subunit EXO70i, involved in the tethering of post-Golgi secretory vesicles and operational in tip growth. The localization of EXO70i in root nodules and arbusculated roots was strictly associated with the tips of infection threads and the tips of arbuscular fine branches, but the distribution of synaptotagmins on membrane subcompartments was broader and includes lateral parts of infection threads, the membrane of unwalled droplets as well as the symbiosomes. The double silencing of synaptotagmins caused a delay in rhizobia release and blocks symbiosome maturation confirming the functional role of synaptotagmins. In conclusion: synaptotagmin-dependent membrane fusion along with tip-targeted exocytosis is operational in the formation of symbiotic interface. Keywords: symbiosis, synaptotagmi1, membrane repair, interface membrane, root nodule, arbuscular mycorrhiza, Medicago truncatula